ANALISIS PEMBIAYAAN KPR DENGAN AKAD MURABAHAH BIL AL WAKALAHDI BTN SYARIAH KC MEDAN - Lubis, Mega Yuliana; Fithri, Fauza; Fadilla A.P, Nur; Wulandari, Riska; Zuriati, Zuriati; Sari, Chyntia Kemala (Proceeding International Seminar of Islamic Studies, 2024)
This research is motivated by the combination of the concepts of murabahah and Al wakalah in providing Home Ownership Credit (KPR) financing by Bank BTN Syariah KC Medan. The mortgage financing process begins with a wakalah contract, followed by a murabahah contract. The research method used is a study of previously existing literature. The research results show that the management of KPR financing at Bank BTN Syariah KC Medan is in accordance with applicable procedures, including the stages of applying for financing, disbursing funds and binding collateral through a notary. This financing aims to provide benefits for all parties involved, namely customers, developers, and Bank BTN Syariah KC Medan, by referring to the Fatwa of the National Sharia Council (DSN) regarding Murabahah (No: 04/DSN-MUI/IV/2000) and Wakalah (No: 10/DSN-MUI/IV/2000)